ChemInform Abstract: Catalytic Thiomethylation of Carboxylic Acid Hydrazides. Issue 14 (8th April 2014) - Khairullina, R. R.; Akmanov, B. F.; Kunakova, R. V.; Ibragimov, A. G.; Dzhemilev, U. M.
Abstract N′, N′‐bis(sulfanylmethyl)carbohydrazides and N‐substituted dithiazepanes, dithiazocanes, and dithiazonanes are efficiently obtained by thiomethylation of carboxylic acid hydrazides mediated by transition metal‐based and rare earth‐based catalysts.